Preparing for a Successful Faculty Career Achieving Career Excellence as a Faculty Member - Fleming, Robert S. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book provides valuable information and practical insights regarding preparing for and pursuing a successful faculty career. It offers essential guidance through sequential chapters that consider the various stages of a successful faculty career, including what faculty members need to know with respect to each lesson and the role of each topic in contributing to career success. Each lesson also provides useful career guidance regarding things that faculty members should do as well as avoid doing during each stage of a faculty career. The book is designed to serve as an essential learning tool in related career preparation courses as well as a valuable self-study and reference source for faculty members. The unfortunate reality is that most graduate programs do not provide essential career guidance regarding the roles and responsibilities of becoming and succeeding as a faculty member. The phrase "hidden curriculum" has been used to describe this unfortunate reality. New faculty members often discover that they are expected to know so many essential things once they become a faculty member. The mission of this book is, therefore, to contribute to the success of readers throughout their careers as faculty members and enhance their ability to meet and exceed the expectations of their students, institution, and other stakeholders. The various lessons are designed to enhance faculty success throughout one's career as well as the meaningfulness and pleasure of one's faculty career.
Keywords: Career education; Maturation (Psychology).; Professional education; Vocational education; Education, Higher; School management and organization; School administration; Career Skills; Personal Development; Professional and Vocational Education; Higher Education; Organization and Leadership